Advances in Functional Assemblies for Regenerative Medicine. Issue 16 (November 2015) - Palma, Matteo; Hardy, John G.; Tadayyon, Ghazal; Farsari, Maria; Wind, Shalom J.; Biggs, Manus J.
Abstract : The ability to synthesise bioresponsive systems and selectively active biochemistries using polymer‐based materials with supramolecular features has led to a surge in research interest directed towards their development as next generation biomaterials for drug delivery, medical device design and tissue engineering.